2017
DOI: 10.1080/20477724.2017.1380945
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity and specificity of a urine based Rapid Diagnostic Test for the diagnosis of plasmodium falciparum in a malaria endemic area in Odisha, India

Abstract: Results of this study are promising. Larger studies are needed to assess whether RDTs using urine could serve as a practical, reliable method for the detection of P. falciparum in a non-invasive manner where invasive blood taking is less feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
(15 reference statements)
3
15
0
Order By: Relevance
“…A high PPV of >90% is an indication that urine has good potentials of being a specimen for malaria diagnosis. Similar findings were also reported by Buppan et al, (2010) and Samal et al, (2017). An improvement in the sensitivity of the kits may enable low levels of malaria antigen found in urine to be detected (Genton et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A high PPV of >90% is an indication that urine has good potentials of being a specimen for malaria diagnosis. Similar findings were also reported by Buppan et al, (2010) and Samal et al, (2017). An improvement in the sensitivity of the kits may enable low levels of malaria antigen found in urine to be detected (Genton et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…Genton et al (1998) reported 84% ® sensitivity for a blood based mRDT (ParaSight -F test) with blood and 26% with urine as specimen for malaria testing. Similar findings were also reported by Buppan et al (2010), Anchinmane and Shedge (2016) and Samal et al (2017). The lower sensitivity might be due to the degradation or proteolytic cleavage of HRP2 excreted in urine (Ehrich et al, 1985;Mharakurwa et al, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…Although a higher sensitivity has been recorded in urine samples from India [41], detection rates and sensitivities for mRDT on saliva and urine recorded in this study were higher than previously reported across sub-Saharan Africa [28,29]. This may be due to higher antigen levels in the samples and/or their minimal degradation since all specimens were analysed almost immediately after collection [24] and not stored [42] or spun [27] to potentially reduce the antigen concentration or activity prior to analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies attempted to evaluate the use of non-blood samples to detect malaria antigens. In India, the sensitivities of urine in two different studies were found to be 38% [ 21 ] and 86.67% [ 22 ]. Like this study, rapid diagnostic test kits intended to be used for detecting malaria antigens in blood were used.…”
Section: Discussionmentioning
confidence: 99%